A alma e o cosmos: o “todo em tudo” (ὅλος πανταχοῦ) na cosmologia plotiniana - Gomes, Rafael Vieira [UNIFESP] (2019)
The Plotinian Cosmology encloses two fundamental theses we aim to comprehend and present, namely: 1) the cosmos is an alive and wise oneness, the stoic and platonic inspirated ―total animal‖ (πάντα δὲ ζῴου) in which every ―being‖ is integrated and in sympathy with the wholeness; and 2) that wholeness is entirely and absolutely present in every single particle of the sensible universe, without any fragmentation or separeteness. This second thesis more properly Plotinian which we call ―all in all‖ (ὅλος πανταχοῦ) embraces the main focal point of our research, even though the last encompasses and is directly associated with the first. But in spite of that as we‘ll see the subject of omnipresence of the totality into the sensible depends on the burgeoning of its psychology and his theory of the ―Cosmos Soul‖ as well as the relation the Soul stabilishes with matter in its conformity to the sensible. In view of the platonism aporia especially from Aristotle‘s critics on elucidating the means of the union between the Soul and the matter, Plotinus elaborates a potent review of the ―participation doctrine‖ as a possible reply to the Aristotelian critics on the Platonic ―dualism‖. In Plotinus, the duality (form and matter; sensible and intellegible; soul and body) integrates itself into an undivisive and omnipresent unity without whatsoever missing the presentation of distinct ―levels‖ with specific characteristics and properties. Our purpose is finding and leading the argumentative ―path‖ in the Enneads, in which Plotinus tries to demonstrate and expose these theses from their foundation. Starting from the critics to the materialism and the assembly of his concept of Soul on his debates with the main traditional Greek schools; through the relationship between the Soul and matter and thus the sensible connection with all reality hypostatic ―levels‖; up to the consequences for the cosmos and individual souls (human beings) of unity and omnipresence of the totality into the sensible.